Associations between Smartphone Usage with Upper-Body Abnormalities, Obesity, Mental Wellbeing and Physical Fitness of High-School Male Students - Sara Bagheri; Sheida Ranjbari; Hassan Shafaei; Saeed Ghorbani (International Journal of School Health, 2025)
Background: The growing prevalence of smartphone usage among adolescents has not been adequately addressed in terms of its impact on their physical and mental health in prior research. Therefore, the objective of this study was to explore the relationships between smartphone usage and upper body abnormalities, obesity, mental well-being, and physical fitness among male high school students.Methods: This was a descriptive correlational study. The statistical sample comprised 384 male students, with a mean age of 17.04 years (±0.83), from high schools situated in the 5th district of Tehran, Iran in 2023. Smartphone usage was measured by asking “How much (in hours) do you use smartphones on average during day”. Upper-body-abnormalities was measured using plastic goniometer and flexible ruler. DASS-21 was used for measuring mental wellbeing. Push-up test was used for assessing physical fitness. The data were analyzed using the independent t-test and the Pearson correlation test.Results: Smartphone usage demonstrated a significant correlation with body mass index (BMI) (r=0.527, P<0.001), forward head posture (r=0.396, P<0.001), and thoracic kyphosis (r=0.442, P<0.001). In contrast, no significant relationships were found between smartphone usage and lumbar lordosis (r=0.050, P=0.452), depression (r=-0.029, P=0.680), anxiety (r=0.058, P=0.481), or stress (r=-0.084, P=0.268). Additionally, a significant association was observed between smartphone usage and push-up performance (r=-0.352, P<0.001).Conclusions: Smartphone addiction has harmful effects on head and neck abnormalities, obesity and physical fitness, but it could not negatively affect a person’s mental wellbeing. These findings can be used as a warning signal to limit the excessive usage of and dependency on smartphones in male adolescents.